PENGARUH PENERAPAN SISTEM MANAJEMEN SUMBER DAYA PERUSAHAAN (ERP) DALAM MENINGKATKAN KINERJA MANAJEMEN RANTAI PASOK (SCM) PT AOHAI TECHNOLOGY INDONESIA - Butarbutar, Hotni Mutiara; Nicholas, Nicholas; Larissa, Jesslyn; Yuki, Narumi; Liu, Lisa Carline; Qadri, Rizni Aulia (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2023)
In this era of globalization, people's demands are increasing, pushing companies inthe world to progress. However, companies often find it difficult to deal with andmanage company resources. One of them is the company PT Aohai TechnologyIndonesia which is engaged in manufacturing, Enterprise Resource Planning (ERP)is here to be a solution to this problem. At its inception, PT Aohai did not use aresource management system. However, due to increasing production capacity andcompany competition, PT Aohai Technology Indonesia tries to provide the best forcustomers, both in terms of products and systems by using a management system,namely the Enterprise Resource Planning (ERP) system. This study uses aqualitative approach and conducts interviews and direct observation of PT Aohaiworkers to obtain data. With this ERP system, the company's management systemis greatly assisted because there are features that are supported in the managementsystem.Keywords: ERP System, Supply Chain Management, PT Aohai Technology